The role of the triglyceride-glucose index as a biomarker of cardio-metabolic syndromes - Verena Gounden; Sridevi Devaraj; Ishwarlal Jialal (Lipids in Health and Disease)
Abstract Background The Triglyceride-glucose (TyG) index represents a simple, cost-effective, and valid proxy for insulin resistance. This surrogate marker has also been proposed as a predictor of metabolic and cardiovascular disease (CVD). In this descriptive review, we aimed to assess the utility of the TyG index as a predictive biomarker of cardiometabolic diseases. Methods A search was conducted in PubMed, and Web of Science to identify cross-sectional and more importantly prospective studies examining the use of the TyG index as a predictive biomarker. The following terms were utilized in addition to the TyG index: “insulin resistance”, “metabolic syndrome”, “diabetes”; “cardiovascular diseases”. Results This descriptive review included thirty prospective studies in addition to cross-sectional studies. Following adjustment for confounding variables, an elevated TyG index was associated with a significantly increased risk for the development of Metabolic Syndrome (MetS), Type 2 Diabetes, hypertension, and CVD. Also in limited studies, the TyG index was associated with endothelial dysfunction, increased oxidative stress and a pro-inflammatory phenotype. Conclusion Overall, our findings support the use of the TyG index as a valid biomarker to assess the risk of developing MetS, T2DM, as well as atherosclerotic cardiovascular disease.